Haitian Immigrant Women: A Cultural Perspective - Stafford, Susan H. Buchanan (Anthropologica, 2022)
Although women have always played an important role in the immigration and resettlement process, this role has not always been acknowledged or explored in great detail by scholars. This article examines the case of Haitian women, focusing upon their role in the immigration process, integration into the labor force, and changes in domestic and social patterns within the Haitian community of New York City. It presents a cultural approach to the immigration experience, with an emphasis on Haitian women's perceptions and attitudes about that experience. The article argues that an analysis of immigration and a population's subsequent adaptation is incomplete without an understanding of both the female role in the process and female perceptions of that experience.